Isolation of Stenotrophomonas maltophilia in asymptomatic lung transplant recipients: effects of treatment on eradication and outcome. Issue 8 (22nd June 2016) - Hofmann, Patrick; Hombach, Michael; Seifert, Burkhardt; Schuurmans, Macé M.; Bürgi, Urs; Isenring, Bruno; Mueller, Nicolas J.; Kohler, Malcolm; Benden, Christian; Huber, Lars C.
Abstract: In this retrospective, single‐center data analysis, we audited our clinical practice to treat Stenotrophomonas maltophilia in asymptomatic lung transplant recipients (LTRs). Eighteen LTRs with confirmed isolation of S. maltophilia were identified. Twelve of these LTRs have been treated with antibiotics, while 6 were managed without treatment. Treatment was based on antibiograms (trimethoprim/sulfamethoxazole [TMP/SMX] (8/12), levofloxacin (1/12), or both (3/12). Clearance (12/12 vs 6/6), eradication (10/12 vs 3/6, P =.27), and freedom from S. maltophilia recurrence (83%±11% vs 40%±22% after one year, log‐rank P =.09) were not found to differ significantly between treated and untreated patients. None of the patient groups showed significant changes in lung function or biochemical variables. Creatinine levels at the end of the study period were found to be higher in treated patients compared to the untreated group ( P =.049). De novo acquired TMP/SMX resistance in S. maltophilia strains was not observed. These results indicate no evidence that antibiotic treatment for S. maltophilia in asymptomatic LTRs alters lung function or the clinical outcome.